Unilocular ossifying fibroma of the mandible misdiagnosed as a radicular cyst: Case report - Ömür Dereci (Cumhuriyet University, 2016)
Ossifying fibroma is a benign fibro-osseous lesion which arises mostly on mandibular molarpremolarregion. Ossifying fibroma may be asymptomatic or may cause buccolingual expansion.The localization of the lesion is mainly on non-tooth bearing areas of the jaws. Radiographicallythe lesion is presented with a range of radiographic patterns including pure radioluscency, mixradiolucency-radiopacity or pure radioopacity. Ossifying fibroma is always well-demarcated. Inthis case report, the surgical treatment of a misdiagnosed unilocular ossifying fibroma which isin relation with mandibular second molar radix is presented.